2012
DOI: 10.2495/eid120311
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring ecosystem health of the Terminos Lagoon region using heavy metals as environmental indicators

Abstract: The Terminos Lagoon region is one of the most important biodiversity hotspots of Mexico and Mesoamerica. However, this high biodiversity is threatened by the activities of the Mexican oil industry, urban development, and land use change in the watersheds of the rivers that drain into it. This study presents the results of a monitoring program undertaken from 2006 to the present using heavy metals (Cd, Pb, Hg, Cu, Zn, As, Al, V and Cr) as environmental indicators. Heavy metals were measured in water, sediments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Besides, these communities display a highly diversified array of functional genes involved in the resistance to environmental stress. We observed genes involved in the resistance to general stressors such as oxygen limitation and antibiotics (Tetracycline, Vancomycin), but more importantly to stressors directly observed in this lagoon, such as osmotic stress (Medina‐Gómez et al ., ), heavy metals (Vazquez et al ., ; Benitez et al ., ) and numerous pollutants such as PAH (e.g., Fluorene, Chlorocyclohexane; Norena‐Barroso et al ., ) or PCBs (Gold‐Bouchot et al ., ; Diaz‐Gonzalez et al ., ; Carvalho et al ., ). Altogether, this suggests that the microbial metacommunity has the functional potential to realize important ecological processes and maintain them within a naturally changing environment (i.e., a lagoon) under strong and multiple anthropogenic pressures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, these communities display a highly diversified array of functional genes involved in the resistance to environmental stress. We observed genes involved in the resistance to general stressors such as oxygen limitation and antibiotics (Tetracycline, Vancomycin), but more importantly to stressors directly observed in this lagoon, such as osmotic stress (Medina‐Gómez et al ., ), heavy metals (Vazquez et al ., ; Benitez et al ., ) and numerous pollutants such as PAH (e.g., Fluorene, Chlorocyclohexane; Norena‐Barroso et al ., ) or PCBs (Gold‐Bouchot et al ., ; Diaz‐Gonzalez et al ., ; Carvalho et al ., ). Altogether, this suggests that the microbial metacommunity has the functional potential to realize important ecological processes and maintain them within a naturally changing environment (i.e., a lagoon) under strong and multiple anthropogenic pressures.…”
Section: Discussionmentioning
confidence: 99%
“…These three sets of communities are composed of organisms adapted to the aquatic environment. In addition, the presence of numerous organic and chemical pollutants (polynuclear aromatic hydrocarbons: Norena‐Barroso et al ., ; pesticides and PCBs: Carvalho et al ., ; heavy metals: Benitez et al ., ), which have accumulated in the Terminos lagoon since the 1970s could have acted as selective forces, leading to the detection in the communities metagenome of genes related to the degradation of these compounds or the resistance to their harmful effects. It was recently reported using a similar tool (i.e., Geochip 5) that functional gene richness increases in heavy metal contaminated sediments (Jie et al ., ), which could be also the case in the Terminos lagoon, leading to the observed functional similarity across habitats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Values of both heavy metals and pesticides in biopsies were low compared to those recorded in other studies. In the Terminos Lagoon area, high Cadmium has not been found in fish and sea turtles egg samples, but in shrimp, bottlenose dolphins (blubber) and manatee (blubber) the mean concentrations were 0.1027, 0.3069 and 0.0159 ppm, respectively (Benítez et al [9]). Delgado-Estrella et al [10] reported low levels in cadmium and no traces of lead, however zinc concentrations were very high.…”
Section: Heavy Metals Contents In Manatee Bone Samplesmentioning
confidence: 99%
“…Benítez et al [9] reported that cadmium, lead and chrome highest levels were found in sediments and some crustaceans near Ciudad del Carmen, Campeche when they performed a heavy metals spatial analysis at the Terminos Lagoon, suggesting an anthropogenic source for these pollutants.…”
Section: Heavy Metals Contents In Manatee Bone Samplesmentioning
confidence: 99%